Polydopamine-mediated superlyophobic polysiloxane coating of porous substrates for efficient separation of immiscible liquids - Mai, Van Cuong (2022)
Lyophobic membrane has the potential to separate immiscible liquids. However, the multistep fabrication and limited option of materials have created major challenges for their practical application. Here, a strategy to fabricate superlyophobic materials is presented by using polydopamine (PDA) as an intermediate coating. The results demonstrate that PDA nanoparticles deposited on diverse substrates can direct the subsequent formation of polysiloxane microsheets (PSMSs), which increases surface roughness and results in superlyophobicity towards high surface tension (ST) liquids and superlyophilicity to liquids with ST of 33 mN m-1 and below. Superlyophobic membranes fabricated from stainless steel mesh, cotton fabric, and filter papers show high efficiency for continuous separations of chloroform/water (>96%) and carbon tetrachloride/formamide (>97%). In addition, superlyophobic melamine foam and polyurethane foam can absorb various low ST liquids with capacities ranging from 53 to 120 g g-1 and from 26.5 to 52.5 g g-1, respectively, revealing the efficient separation of a broad range of immiscible liquids. All of the as-prepared superlyophobic materials show excellent regeneration with insignificant change of separation efficiency over 10 cycles. The preparation route for superlyophobic materials in this work introduces a new strategy for the separation of immiscible liquids by both batch absorption and continuous filtration treatment.